The gut microbiota influences neurodegenerative diseases through the gut-brain axis: molecular mechanisms and effects on immune function - Yang, Jiaheng; Song, Xiangzhun; Yan, Su; Li, Qianxun; Yang, Wenying (Frontiers in Immunology, 2026)
The pathogenesis of neurodegenerative diseases (NDDs), including Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS), is complex and multifactorial. Recent studies indicate that the microbiota-gut-brain axis (MGBA) plays a crucial role in the development and progression of NDDs. The MGBA concept reveals a complex bidirectional regulatory network between the gut microbiota and the central nervous system (CNS), linking them through immune, neural, endocrine, and metabolic pathways. This review summarizes the components of the MGBA, communication pathways between gut microbiota and the brain, and mechanisms by which gut microbiota influence the onset and progression of NDDs. Finally, preclinical therapeutic approaches for NDDs are discussed, evaluating preclinical trial data for probiotics, prebiotics, and fecal microbiota transplantation.